Location dependent coordination chemistry and MRI relaxivity, in de novo designed lanthanide coiled coils. Issue 3 (11th January 2016) - Berwick, Matthew R.; Slope, Louise N.; Smith, Caitlin F.; King, Siobhan M.; Newton, Sarah L.; Gillis, Richard B.; Adams, Gary G.; Rowe, Arthur J.; Harding, Stephen E.; Britton, Melanie M.; Peacock, Anna F. A.
Abstract : Lanthanide binding site translation linearly along a coiled coil has a large impact on stability, coordination chemistry, and MRI relaxivity. Abstract : Herein, we establish for the first time the design principles for lanthanide coordination within coiled coils, and the important consequences of binding site translation. By interrogating design requirements and by systematically translating binding site residues, one can influence coiled coil stability and more importantly, the lanthanide coordination chemistry. A 10 Å binding site translation along a coiled coil, transforms a coordinatively saturated Tb(Asp)3 (Asn)3 site into one in which three exogenous water molecules are coordinated, and in which the Asn layer is no longer essential for binding, Tb(Asp)3 (H2 O)3 . This has a profound impact on the relaxivity of the analogous Gd(iii ) coiled coil, with more than a four-fold increase in the transverse relaxivity (21 to 89 mM −1 s −1 ), by bringing into play, in addition to the outer sphere mechanism present for all Gd(iii ) coiled coils, an inner sphere mechanism. Not only do these findings warrant further investigation for possible exploitation as MRI contrast agents, but understanding the impact of binding site translation on coordination chemistry has important repercussions for metal binding site design, taking us an important step closer to the predictable and truly de novo design of metal binding sites, for new functional applications.